2022
DOI: 10.1186/s12887-022-03257-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between match participation, maturation, physical fitness, and hormonal levels in elite male soccer player U15: a prospective study with observational cohort

Abstract: Objectives The aims of this study were to analyze the relationships between minutes of play (MP) and maturity status, fitness, and hormonal levels and to explain how those measures influence the time of play. Methods Twenty-six youth soccer players U15 participated in this study over a full-season period. Anthropometric measures, maturity status, growth hormone (GH), insulin-like growth factor and physical levels such as maximal oxygen uptake (VO2m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Despite not being verified RAE in the shallow races in the under-16 in the feminine, very practised, there is a greater incidence of those born in the first semester concerning the second semester, compared to the races with hurdles, where there is more balance between the births. In this case we should also consider the explanation of Beunen et al [ 32 ], emphasizing that at the peak of maturation in girls there is an increase in mass. According to Garlipp et al [ 33 ], this gain in body mass is due to the increase in height and fat mass of girls, thus allowing the inference that this would not be an advantage for shallow tests in athletics.…”
Section: Discussionmentioning
confidence: 84%
“…Despite not being verified RAE in the shallow races in the under-16 in the feminine, very practised, there is a greater incidence of those born in the first semester concerning the second semester, compared to the races with hurdles, where there is more balance between the births. In this case we should also consider the explanation of Beunen et al [ 32 ], emphasizing that at the peak of maturation in girls there is an increase in mass. According to Garlipp et al [ 33 ], this gain in body mass is due to the increase in height and fat mass of girls, thus allowing the inference that this would not be an advantage for shallow tests in athletics.…”
Section: Discussionmentioning
confidence: 84%
“…According to Nobari et al [67], we can say that TM and TS values are lower than our study throughout the season. In an another study, Nobari et al [8] indicated that TM values average 1.2 A.U. during the season in under-16 soccer players.…”
Section: Discussionmentioning
confidence: 94%
“…According to time-motion analysis, elite professional adult soccer players cover a total distance of approximately 10-12 km at an average intensity close to the anaerobic threshold (80-90% of maximum heart rate) [5,6], and they perform 1350 activities every 4-6 seconds during the game. Approximately 150 to 250 of these activities are short, intense, and explosive activities associated with maximal sprint, acceleration, and change of direction [7,8]. On the other hand, the activity profiles of young soccer players (distance covered, high-intensity activity and sprinting) during the match are low.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to complete the shuttle run on two successive occasions resulted in the termination of the test and the distance covered represented the final test Life 2023, 13, 1503 6 of 17 result. The club's coaches habitually conducted the YYIRT1 during the season for all agecategories, and the test leaders were also highly familiar with all testing procedures [40,41].…”
Section: Physical Fitness Parameters Yo-yo Intermittent Recovery Test...mentioning
confidence: 99%